Reduction in the choking phenomenon in elite diving athletes through changes in gut microbiota induced by yogurt containing bifidobacterium animalis subsp. lactis BB-12: A quasi experimental study - Dong, W.; Wang, Y.; Liao, S.; Lai, M.; Peng, L.; Song, G. (Microorganisms, 2020)
Objective: The aims of this study are as follows: (1) to understand the relationship between gut microbiota and the choking phenomenon in diving athletes, and (2) to regulate the gut microbiota in diving athletes by drinking yogurt containing Bifidobacterium animalis subsp. lactis BB-12 and observe changes in the choking phenomenon in diving athletes. Methods: Experiment 1: A total of 20 diving athletes were tested in low- and high-pressure situations. Gut microbiota (n = 18) composition was then determined and di erences in the gut microbiota composition among diving athletes who presented choking vs. no choking were identified. Experiment 2: Atotal of 16 divers who presented choking were divided into a high yogurt group (n = 6) and a low yogurt group (n = 10) for 15 days. Results: (1) The content of Veillonellaceae in divers who presented choking was significantly higher when compared to divers who did not present choking (p < 0.05). Bifidobacteriaceae (r = ..0.52, p < 0.05) and Lactobacillaceae (r = ..0.66, p < 0.05) were negatively correlated with the choking index. (2) During experiment 2, the average daily intake of the high yogurt group was 611.78 94.94 mL and the average daily intake of the low yogurt group was 338 71.45 mL and the abundance of Bifidobacteriaceae was significantly higher in the high yogurt group than in the low yogurt group. After the experiment, the choking index in the high yogurt group became significantly lower than that of the low yogurt group (z = ..3.26, p < 0.001). Conclusion: The intake of yogurt containing B. animalis subsp. lactis can increase the abundance of Bifidobacteriaceae in elite diving athletes and their performance under high pressure. Hence, gut microbiota may a ect the choking phenomenon in elite diving athletes.